Sex Differences in Breast Cancer: Implications for Immunotherapy and Combination Treatments - Muhammad Waqas; Razia Bashir; Humera Ambreen; Muhammad Arshad (AMERICAN JOURNAL OF CASE REPORTS AND CLINICAL IMAGES, 2025)
Background: Sex differences in breast cancer are critical determinants of tumor biology, treatment responses, and clinical outcomes. Despite breast cancer’s predominance in women, men are also affected, with distinct biological and clinical characteristics. However, research on sex-specific influences in breast cancer remains limited, particularly regarding immunotherapy and combination treatments. Objectives: This study explores the molecular, genetic, and immune-related mechanisms underlying sex differences in breast cancer. It evaluates the implications for immunotherapy and combination treatments and emphasizes the need for personalized, sex-specific therapeutic approaches. Methods: A comprehensive review of current literature was conducted to examine sex differences in breast cancer, focusing on hormonal, genetic, and immunological mechanisms. Research on immune response variations and clinical trial data related to breast cancer treatment outcomes was analyzed. Evidence from studies on immunotherapy and combination treatment strategies was reviewed to identify sex-specific outcomes, therapeutic challenges, and potential personalized treatment approaches. Results: Sex hormones, chromosomal differences, and immune system variations significantly influence tumor behavior and therapeutic responses. Men and women exhibit different outcomes with immune checkpoint inhibitors, with variations in efficacy and adverse effects. Combination treatments involving immunotherapy and hormonal or chemotherapy-based approaches show potential but require sex-specific considerations. Conclusions: Sex differences must be recognized as a critical determinant in breast cancer treatment. Integrating sex as a biological variable in clinical trials and developing sex-specific biomarkers can enhance personalized medicine. 1. Sung, H., Ferlay, J., Siegel, R. L., Laversanne, M., Soerjomataram, I., Jemal, A., & Bray, F. (2021). Global cancer statistics 2020: GLOBOCAN estimates of incidence and mortality worldwide for 36 cancers in 185 countries. CA: A Cancer Journal for Clinicians, 71(3), 209–249. https:// doi.org/10.3322/caac.21660 2. Giordano, S. H. (2018). Breast cancer in men. The Lancet Oncology, 19(1), 12-14. https://doi.org/10.1016/S1470-2045(17)30996-9 3. Rosen, S. F., Chen, S., Klein, R. S., Imoukhuede, P., & Luo, J. (2020). Sex differences in cancer mechanisms. Biology of sex differences, 11(1), 17. https://doi.org/10.1186/s13293-020-00291-x 4. Conforti, F., Pala, L., Bagnardi, V., De Pas, T., Martinetti, M., Viale, G., Gelber, R. D., & Goldhirsch, A. (2018). Cancer immunotherapy efficacy and patients’ sex: a systematic review and meta-analysis. The Lancet. Oncology, 19(6), 737–746. https://doi.org/10.1016/S1470- 2045(18)30261-4 5. Chen, S., Zhang, Z., Zheng, X., Tao, H., Zhang, S., Ma, J., Liu, Z., Wang, J., Qian, Y., Cui, P., Huang, D., Huang, Z., Wu, Z., & Hu, Y. (2021). Response Efficacy of PD-1 and PD-L1 Inhibitors in Clinical Trials: A Systematic Review and Meta-Analysis. Frontiers in oncology, 11, 562315. https:// doi.org/10.3389/fonc.2021.562315 6. Gucalp, A., Traina, T. A., Eisner, J. R., Parker, J. S., Selitsky, S. R., Park, B. H., Elias, A. D., Baskin-Bey, E. S., & Cardoso, F. (2019). Male breast cancer: a disease distinct from female breast cancer. Breast cancer research and treatment, 173(1), 37–48. https://doi.org/10.1007/s10549-018- 4921-9 7. Bhardwaj, P. V., Gupta, S., Elyash, A., & Teplinsky, E. (2024). Male Breast Cancer: a Review on Diagnosis, Treatment, and Survivorship. Current Oncology Reports, 26(1), 34-45. 8. Mavaddat, N., Antoniou, A. C., Mooij, T. M., et al. (2020). Prediction of breast cancer risk based on profiling with common genetic variants. British Journal of Cancer, 122(11), 1659–1667. https://doi. org/10.1038/s41416-020-0849-x 9. Huang, J., Xie, N., Huang, H., et al. (2021). Sex differences in DNA methylation and breast cancer risk. Clinical Epigenetics, 13(1), 124. https://doi.org/10.1186/s13148-021-01149-7 10. Sharma, P., & Allison, J. P. (2020). The future of immune checkpoint therapy. Science, 348(6230), 56–61. https://doi.org/10.1126/science. aaa8172 11. Adams, S., Schmid, P., Rugo, H. S., et al. (2019). Pembrolizumab monotherapy for previously untreated, PD-L1-positive, metastatic triple-negative breast cancer: Cohort B of the phase II KEYNOTE-086 study. Annals of Oncology, 30(3), 405–411. https://doi.org/10.1093/ annonc/mdy518 12. Schmid, P., Adams, S., Rugo, H. S., Schneeweiss, A., Barrios, C. H., Iwata, H., ... & Emens, L. A. (2018). Atezolizumab and nab-paclitaxel in advanced triple-negative breast cancer. New England Journal of Medicine, 379(22), 2108–2121. https://doi.org/10.1056/NEJMoa1809615 13. Waqas, M., Bashir, R., Nohra, L., Feranmi Adeyemo, S., Confidence, D., Tayyab, M., & ur Rahman, S. (2024). Impact of SARS-CoV-2 on Oncogenesis: A Deep Dive into the COVID-19 and Cancer Nexus. Iranian Journal of Blood and Cancer, 16(3), 55-62. 14. Jaillon, S., Berthenet, K., & Garlanda, C. (2019). Sexual dimorphism in innate immunity. Clinical Reviews in Allergy & Immunology, 56(3), 308– 321. https://doi.org/10.1007/s12016-018-8714-9 15. Cortés, J., Cescon, D. W., Rugo, H. S., et al. (2020). KEYNOTE-119: Phase III study of pembrolizumab versus chemotherapy in previously treated metastatic triple-negative breast cancer. Journal of Clinical Oncology, 38(4), 326–336. https://doi.org/10.1200/JCO.19.00365 16. Marra, A., Curigliano, G., & Di Cosimo, S. (2019). Sex differences in cancer immunotherapy efficacy: A systematic review and meta-analysis. Cancer Treatment Reviews, 81, 101871. https://doi.org/10.1016/j. ctrv.2019.101871 17. 17. Demaria, S., Bhardwaj, N., McBride, W. H., et al. (2005). Combining radiotherapy and immunotherapy: a revived partnership. International Journal of Radiation Oncology, Biology, Physics, 63(3), 655–666. https:// doi.org/10.1016/j.ijrobp.2005.06.032 18. Emens, L. A., Adams, S., Barrios, C. H., et al. (2020). Atezolizumab plus nab-paclitaxel as first-line treatment for unresectable, locally advanced or metastatic triple-negative breast cancer: updated efficacy results from the IMpassion130 trial. Annals of Oncology, 31(5), 664–675. https://doi.org/10.1016/j.annonc.2020.02.008 19. Zhang, M., Sun, H., Zhao, S., et al. (2021). Sex differences in cancer immunotherapy efficacy: Comprehensive analysis in a multiinstitutional cohort. Journal of Immunotherapy Cancer, 9(6), e002990. https://doi.org/10.1136/jitc-2021-002990